Study of Serum Magnesium Levels in Type 2 Diabetics - Ranjith kumar GK; Santhosh P (International Journal of Medical Research and Review, 2015)
Introduction: A prospective case control study of serum magnesium levels in relations with micro & macro vascular complications of type 2 diabetes mellitus in J.L.N Hospital Ajmer.Methods: 25 patients of type 2 diabetes mellitus admitted to J.L.N Hospital were included in the study. Also 25 non diabetic patients admitted at the same time were included in the study under the control group.Results: The present study had diabetic patients ranging from 40-80 years. The mean serum magnesium levels were 1.68 mg/dl and 2.02 mg/dl in cases and controls respectively. The mean serum magnesium levels in patients on insulin, OHAs and on OHAs plus insulin were 1.43 mg/dl, 2.14 mg/dl and 1.53 mg/dl respectively. The mean serum magnesium levels in patients with controlled diabetes were 2mg/dl and 1.33 mg/dl in patients with uncontrolled diabetes. The mean serum magnesium levels in patients with and without diabetic retinopathy were 1.44 mg/dl and 2.11 mg/dl respectively. Whereas the mean serum magnesium levels in patients with diabetic nephropathy were 1.31 mg/dl and 2.08 mg/dl in those without nephropathy.Conclusion: Hypomagnesemia is a factor in type 2 diabetes and associated with various complications and duration of diabetes leading to various complications. Hence it is worth measuring serum magnesium levels in patients with type 2 DM and probably correlates their relationship with various complications.